PENINGKATAN LITERASI ANTI-BULLYING BERBASIS EMPATI BAGI SISWA SMP NEGERI SATU ATAP SABRON SARI PAPUA: (ENHANCING EMPATHY-BASED ANTI-BULLYING LITERACY AMONG JUNIOR HIGH SCHOOL STUDENTS IN SABRON SARI PAPUA) - Aisyah; Yasinta Bella Fitriana; Rani Safitri; Novi Wanimbo (LPPM Universitas Muhammadiyah Papua, 2026)
Bullying is an issue in the educational world that is often unnoticed because it is considered part of adolescent social interaction. In fact, this behavior harms students’ psychological and social development. This community service activity (PKM) was carried out at SMP Negeri Satu Atap Sabron Sari, Papua Province, as an effort in early prevention through the enhancement of empathy-based anti-bullying literacy. The purpose of this activity is to increase students’ understanding and empathetic attitudes towards various forms and impacts of bullying. The target of this activity is 36 junior high school students involved in participatory educational activities. The implementation methods include initial observation, delivery of bullying literacy materials, interactive discussions, and anti-bullying visual campaigns. The results of the pre- and post-tests showed an increase in students’ understanding and the growth of collective awareness to provide a safe and inclusive school environment. Therefore, this program is expected to be sustainably developed through continued mentoring and the integration of the material into school activities.